Youth-voice driven after-school science clubs: A tool to develop new alliances in ethnically diverse communities in support of transformative learning for preservice teachers and youth - Rahm, Jrène; Malo, Annie; Lepage, Michel (Alterstice, 2016)
In this paper, we draw on data collected in the context of a three-year action research project that involved the development of after-school science clubs in three high schools in ethnically diverse communities, made possible through a partnership between a university, the schools and the community. We document the evolution of a youth-voice driven science club over time and the kind of transformative learning it supported for youth who are for the most part first-generation immigrants growing up in an underserved urban centre. We also explore how the alliance between the university, the school and the community enriched the learning ecologies of the participating youth and how it was experienced by the instructors and preservice teachers who pursued service learning projects in the clubs as part of their university course work in education. We show how such diverse experiences offer rich insights into ways of building alliances among schools, community resources and the university to support equity-driven practices that are inclusive and supportive of ethnically diverse youth with complex immigration histories.